PATIENT SAFETY IN THE PROCESS OF ORGAN AND TISSUE DONATION AND TRANSPLANT - Aline Lima Pestana Magalhães; abriela Marcellino de Melo Lanzoni; Neide da Silva Knihs; Elza Lima da Silva; Alacoque Lorenzini Erdmann (Universidade Federal do Paraná, 2017)
This article aims to present innovative aspects for the professional practice of the nurse, regarding the diagnosis of brain death in the process of donation and transplantation of organs and tissues, addressing the interfaces between the care management and patient safety. Emphasis is placed on the standardization of processes, used to promote speed, reduction in losses from cardiac arrest with a concurrent increase in actual donations, and reduction of time between the first clinical examination and harvesting of the organ. It allows the team to recognize abnormalities and make the necessary corrections in time. Thus, it is seen that patient safety should be a basis for management's decision-making and interventions, so as to make the care practice of adequate quality.